John Stuart Mill and the paternalism issue - Cornejo Amoretti, Leandro (Derecho & Sociedad, 2017)
The present investigations study the John Stuart Mill thinking and his position towards paternalism justification, taking into account the harm principle elaborated in his book “On Liberty”. Two are the objectives of this paper. In first place, the anti - paternalist tesis sustained by this autor will be analyzed to identify deficiencies and limitations. In second place, it is sought to determine to what extent they actually opposed such interventions, to verify the accuracy of that somewhat extended belief that sees Mill a strong opponent of paternalism. It is concluded that the defects of Mill’s theses are explained in good account due to an excess of optimism in the capacities of human beings for self-regulation, a strong skepticism about the capacity of the State to achieve effective paternalistic measures, granting From an excessively strong and unrealistic weight to individual autonomy, among other erroneous considerations. It is also concluded that it is not correct to say that John Stuart Mill has maintained an extremely broad or almost absolute antipaternalistic thesis. Although his famous principle of harm makes it impossible to validate many measures of this nature, a more detailed review of his entire work shows that Mill admitted the validity of many interventions in adults.